2003
DOI: 10.1097/00005792-200301000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Manifestations in Giant Cell Arteritis

Abstract: Giant cell arteritis (GCA) is a multisystemic vasculitis of elderly people that involves large and medium-sized blood vessels with predisposition to the cranial arteries. Some cranial ischemic manifestations, in particular permanent visual loss, have been widely described. Audiovestibular manifestations have been less commonly reported. In the present study we assessed the frequency and outcome of audiovestibular manifestations in a series of GCA and isolated polymyalgia rheumatica (PMR) patients examined pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 51 publications
3
31
1
1
Order By: Relevance
“…Moreover, no additional improvement in hearing function was observed after another 3 months of treatment. These data suggest that the possible improvement in hearing function may be achieved generally early during the first months after the onset of therapy [16]. In summary, our results support the presence of both auditory and vestibular dysfunction closely related to the vasculitic process in GCA patients.…”
Section: Audiovestibular Manifestations In Systemic Vasculitissupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, no additional improvement in hearing function was observed after another 3 months of treatment. These data suggest that the possible improvement in hearing function may be achieved generally early during the first months after the onset of therapy [16]. In summary, our results support the presence of both auditory and vestibular dysfunction closely related to the vasculitic process in GCA patients.…”
Section: Audiovestibular Manifestations In Systemic Vasculitissupporting
confidence: 79%
“…This fact is even more important in GCA whose presenting manifestation is PMR only, as in these cases low dose prednisone does not prevent the development of blindness. The presence of abnormal vestibular tests in patients presenting with PMR without cranial manifestations of GCA may be considered as a red flag to raise the suspicion of an underlying GCA [16]. Takayasu's arteritis is a chronic vasculitis of unknown etiology that affects the aorta, its major branches, the pulmonary artery and the coronary arteries; it causes headache, absence of arterial pulses, heart failure, renovascular hypertension and ocular and cerebral ischemia.…”
Section: Audiovestibular Manifestations In Systemic Vasculitismentioning
confidence: 99%
“…These authors also concluded that vertiginous complaints were mainly orthostatic and due to general microvascular involvement. Amor-Dorado et al [2003], in a study of patients with giant cell arteritis, reported that the cochlea and the vestibular system were both affected by the disease. The interesting finding in their study is the reversibility of auditory and vestibular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…More rarely, visual loss is caused by central retinal artery occlusion, ischemic retrobulbar neuritis, or occipital infarction in the setting of a stroke involving the vertebrobasilar territory (4). Less common neurologic complications include transient ischemic attacks and cerebral infarctions, in particular in the vertebrobasilar territory (4), and audiovestibular dysfunction (5).…”
Section: Epidemiology Of Gca and Pmrmentioning
confidence: 99%